Benzyl isothiocyanate inhibits invasion and induces apoptosis via reducing S100A4 expression and increases PUMA expression in oral squamous cell carcinoma cells - Ma,Lei (2019)
Benzyl isothiocyanate (BITC) has been shown to inhibit invasion and induce apoptosis of various types of cancer. However, its role on human oral squamous cell carcinoma (OSCC) cells is still not well elucidated. In the present study, we investigated the effect of BITC on apoptosis and invasion of SCC9 cells, and its underlying mechanisms in vitro and in vivo. SCC9 cells were exposed to BITC (5 and 25 μM) for 24 and 48 h. Cell growth, apoptosis, invasion, and migration were detected in vitro by MTT, FITC-conjugated annexin V/propidium iodide staining followed by flow cytometry, Matrigel-coated semi-permeable modified Boyden, and wound-healing assay. S100A4, PUMA, and MMP-9 expressions were detected to investigate its mechanisms. Xenotransplantation experiments were used to investigate the role of BITC on tumor growth and lung metastasis. BITC inhibited cell viability and induced cell apoptosis in a dose- and time-dependent manner through upregulation of PUMA signals. BITC inhibited cell invasion and migration by downregulation of S100A4 dependent MMP-9 signals. The ip administration of BITC reduced tumor growth but not lung metastasis of SCC9 cells subcutaneously implanted in nude mice. BITC treatment activated pro-apoptotic PUMA and inhibited S100A4-dependent MMP-9 signals, resulting in the inhibition of cell growth and invasion in cultured and xenografted SCC9 cells. Thereby, BITC is a potential therapeutic approach for OSCC.